Automatic brightness control of the handheld device display with low illumination - Tien-Yan Ma; Chin-Yang Lin; Shu-Wei Hsu; Che-Wei Hu; Ting-Wei Hou (2012 IEEE International Conference on Computer Science and Automation Engineering, 2012)
The automatic brightness control is a common functionality on the smartphone. Either Android phones or iPhones enable this capability by using the light sensor which located on the front panel. Unfortunately, the automatic brightness control is unsatisfactory on these two types of smartphones where the user always struggles with the brightness setup to adapt to the ambient light with various intensities. In this paper, a novel automatic brightness control method which is suitable for low illumination is proposed. We take advantage of the front panel camera on the smartphone and face detection technics to capture the image of user's face and background. With low ambient brightness, the proposed scheme calculates the contrast ratio between user's face and background to determine the optimum screen brightness.